THE INFLUENCE OF STUDENT PERCEPTIONS ABOUT COOPERATIVE LEARNING ON LEARNING MOTIVATION AND ACHIEVEMENT OF CLASS IV STUDENTS AT SDN PACE III - Abdul Basir Muhammad; Darsan Darsan (Journal of Education Technology and Inovation, 2022)
This study aims to determine 1) Knowing the effect of student perceptions of cooperative learning on the motivation of grade IV/a SDN Pace III academic year 2019/2020?. This type of research is causal quantitative research. Determination of the research area is done by using a purposive sampling area technique. In this study, the method of determining respondents was saturated sampling. The method used by the author in collecting data in this study are 1) Observation (observation), 2) Interview (interview), and 3) Documentation. Pre-study includes testing research instruments both validity and reliability. While post-research is a test conducted to determine the results of research that will determine the acceptance or rejection of a research hypothesis. From the results of this study, the authors can conclude that the results of the hypothesis test of students' perceptions of cooperative learning (jigsaw) significantly affect the learning achievement of grade IV/A students at SD Negeri Pace III, Silo District, Jember Regency in social studies subjects for the 2019/2020 academic year which can be seen from the results of the regression coefficient test where Ho (regression coefficient is not significant) is rejected because the empirical t statistic > theoretical t statistic (7.285 > 2.05) and the probability of 0.000 is less than 0.05.